A New mHealth application to support treatment of sleep apnoea patients. (January 2017) - Isetta, Valentina; Torres, Marta; González, Kevin; Ruiz, Concepción; Dalmases, Mireia; Embid, Cristina; Navajas, Daniel; Farré, Ramon; Montserrat, Josep M
Introduction: Continuous positive airway pressure (CPAP) is the first-choice treatment for obstructive sleep apnoea (OSA), but adherence is frequently suboptimal. Innovative, patient-centred interventions are, therefore, needed to enhance compliance. Due to its low cost and ubiquity, mobile health (mHealth) technology seems particularly suited for this purpose. We endeavoured to develop an mHealth application called "APPnea, " aimed at promoting patient self-monitoring of CPAP treatment. We then assessed the feasibility and acceptability of APPnea in a group of OSA patients. Methods: Consecutive OSA patients used APPnea for six weeks. APPnea gave patients daily reminders to answer three questions about their OSA treatment (CPAP use, physical activity, and diet) and prompted them to upload their body weight weekly. Answers were saved to a secure server for further analysis. After completing the study, patients gave their anonymous opinions about APPnea. Results: We enrolled 60 patients with OSA receiving CPAP treatment. The mean age was 56 ± 10 years and the apnoea–hypopnea index was 47 ± 25 events/hour. In total, 63% of participants completed the daily questionnaire for more than 66% of the study period. Objective CPAP compliance was generally high (5.3 ± 1.6 hours/night). In a subset of 38 patients naïve to CPAP, those who used APPnea regularly had significantly higher CPAP compliance. Satisfaction levels were high for the majority of users. Conclusion: This mHealth intervention is not only feasible but also satisfactory to patients. Although larger randomized trials and cost-effectiveness studies should be performed, this study shows that APPnea could promote participation and improve compliance among patients with OSA, thereby improving outcomes.